Slow Release of GA3 Hormone from Polymer Coating Overcomes Seed Dormancy and Improves Germination - Alexandra J. S. Larson; Maureen M. Cartwright; Whitney D. Jones; Katrina Luce; Mei-Yu Chen; Kate Petersen; Shannon V. Nelson; David J. Michaelis; Matthew D. Madsen (Plants, 2023)
Seed dormancy often hinders direct seeding efforts that are attempting to restore degraded landscapes. Gibberellic acid (GA3) can be applied to physiologically dormant seeds to induce germination, but this hormone is rarely effective, as it can degrade or be leached from the seed. We tested different polymer matrixes (polylactic acid, polyvinylpyrrolidone, and ethylcellulose) to apply and slowly release GA3 to the seed. These polymers were tested as seed coatings in either a powder, liquid, or a combination of powder and liquid forms. We found that a liquid ethylcellulose/GA3 coating generally outperformed the other polymers and applications methods using our test species Penstemon palmeri. With this top-performing treatment, seed germination was 3.0- and 3.9-fold higher at 15 °C and 25 °C, respectively. We also evaluated the liquid ethylcellulose/GA3 coating on P. comharrenus, P. strictus, P. pachyphyllus, and P. eatonii. Again, the coating had a strong treatment response, with the degree of difference related to the relative level of dormancy of the species. Growth studies were also performed in pots to ensure that the side effects of GA3 overdosing were not present. Here, we found minimal differences in root length, shoot length, or biomass between plants grown from untreated and GA3-coated seeds.